Batteries to Keep Solar‐Driven Water Splitting Running at Night: Performance of a Directly Coupled System. Issue 4 (27th January 2022) - Kin, Li-Chung; Astakhov, Oleksandr; Lee, Minoh; Haas, Stefan; Ding, Kaining; Merdzhanova, Tsvetelina; Rau, Uwe
Abstract : Direct solar‐powered hydrogen generation (so‐called "green" hydrogen) is promising as a renewable fuel that can be generated anywhere there is sunshine and water. Many attempts are made to integrate a water electrolyzer (EC) and solar cell at different levels (a so‐called artificial leaf) to take advantage of the reduced losses from the lack of wiring and optionally increased portability afforded by an integrated unit. However, in many cases, EC catalysts degrade as electrodes depolarize when shut down at night. Much less attention is paid to the need for a minimum current across the EC under insufficient illumination to prevent excessive cyclic degradation. Directly coupling a battery to keep an artificial leaf running at night can address this need and, in theory, also increase solar‐to‐hydrogen (STH) efficiency. A seven‐cell silicon heterojunction module, two bifunctional NiFeMo ECs in series, and a commercial Li‐ion NMC battery are selected to provide the same amount of solar output power despite different working voltages and tested in a series of simulated diurnal cycles. The increased average STH efficiency per cycle (11.4% vs. 10.5% without the battery) is analyzed and discussed with implications for future artificial leaf design and implementation. Abstract : Attaching an appropriately sized, voltage‐matched battery directly to an artificial leaf has the potential to provide self‐sustaining operation with high efficiency. An increased average solar‐to‐hydrogen efficiency per cycle (11.4% vs. 10.5% without battery) using commercially available parts is demonstrated. The results are analyzed and discussed with implications for future integrated artificial leaf design and implementation.